Dampak Maloklusi Terhadap Psikososial Remaja di SMA Negeri 9 Makassar - Saleh, Muhammad; Sainuddin; Bakhtiar; Nur Hijriyati Syam (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Oral health issues in Indonesia remain a serious concern, with 57% of the population experiencing dental problems, yet only 10.2% receive treatment. Malocclusion, which refers to an imbalance in tooth alignment, affects approximately 80% of the population and negatively impacts daily life, including psychosocial aspects. Research shows that malocclusion can affect self-esteem and appearance, requiring more attention in orthodontic care. This study uses an observational analytic method, where subjects are directly observed to investigate the relationship between two or more variables. The researchers only observe the subjects without providing any interventions. The research design used is cross-sectional, aiming to assess the relationship between independent and dependent variables at a single point in time without further analysis. Bivariate analysis using the Chi-Square test shows no significant relationship between malocclusion and psychosocial status among adolescents at SMA Negeri 9 Makassar (p=0.149). Most respondents experienced Class 1 malocclusion with symptoms such as crowding, but their low knowledge and awareness influenced their perception of malocclusion’s impact on social life. Consistent with previous studies, these findings indicate that malocclusion does not significantly affect the psychology of adolescents. Malocclusion is most commonly found among female adolescents at SMA Negeri 9 Makassar